Formulation Development and Invitro Evaluation of Famotidine Gastroretentive Tablets - Sharma, Hrishabh; Sharma, Ashutosh; Pandey, Saurabh; Agarwal, Vikas; Sain, Sunil (Journal of Biomedical and Pharmaceutical Research, 2023)
The present study involves the formulation and evaluation of gastroretentive drug delivery of Famotidine tablets. This type of drug delivery helps to retain the drug in the stomach. The swelling property of the formulation helps to retain the drug in the stomach, by swelling to such an extent so that cannot pass out of the stomach. Preformulation studies which include Organoleptic properties, Bulk and Tapped densities, Carr‘s index, Hausner‘s ratio, Melting point, pH, Solubility, were carried out are as per IP specifications. Drug-excipient compatibility studies were performed which shows that there is no interaction between drug and polymers. Evaluation studies have been performed for tablets include friability, hardness, weight variation, content uniformity, buoyancy studies are as per IP specifications. Drug release studies have been performed by using 0.1N HCl for 12 hrs. These studies have shown that the formulation F4 gave better drug release upto 12 hrs. which is formulated with HPMC K100 M.